Communication Models, Characteristics of Individual Communication - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
The purpose of human communication is to convey and acquire information, as well as to share individual emotions and needs. The success of this process depends on a number of factors. During socialization, every child encounters several communication styles and develops their own – typical – communication techniques along these patterns – with attention also to the by other persons expected behaviours and other influencing factors. Blockage in interaction also can be caused by the reason inherent in the individual’s ability to communicate, as well as by an inappropriately chosen form of communication. The chapter gives a brief overview of the individual characteristics (and disorders) of effective communication, as well as the personality typologies (e.g. DISC-model) that determines our communication style. Solutions that strengthen communication capabilities and support effective interpersonal communication, such as the 5C or 7C communication model, will also be presented.Keywords: effective communication, communication disorder, DISC-model, integrated communication, 5C, 7C,individual communication competences, personality